2011
DOI: 10.1039/c1sc00117e
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous molybdenum sulfide films as catalysts for electrochemical hydrogen production in water

Abstract: Amorphous molybdenum sulfide films are efficient hydrogen evolution catalysts in water. The films are prepared via simple electro-polymerization procedures and are characterized by XPS, electron microscopy and electronic absorption spectroscopy. Whereas the precatalysts could be MoS 3 or MoS 2 , the active form of the catalysts is identified as amorphous MoS 2 . Significant geometric current densities are achieved at low overpotentials (e.g., 15 mA cm À2 at h ¼ 200 mV) using these catalysts. The catalysis is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

85
1,174
4
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,300 publications
(1,267 citation statements)
references
References 34 publications
85
1,174
4
4
Order By: Relevance
“…This H 2 production efficiency is at least 1-2 orders of magnitude greater than in the cases of most of the other MoS 2 -based catalysts of similar mass (Table S2) (derived from the initial linear region of Figure 5a), which were also considerably larger than in the other cases (Table S2) Figure 5d; Figure S9; using efficient catalyst massof 2.39 µg ), which was > 1 order of magnitude greater than in the case of most of the other MoS 2 -based catalysts (Table S1). 1,3,4,6,7,11,14,16,31,32 …”
Section: Catalytic Performance Of 3d Structured S-depletedmentioning
confidence: 99%
“…This H 2 production efficiency is at least 1-2 orders of magnitude greater than in the cases of most of the other MoS 2 -based catalysts of similar mass (Table S2) (derived from the initial linear region of Figure 5a), which were also considerably larger than in the other cases (Table S2) Figure 5d; Figure S9; using efficient catalyst massof 2.39 µg ), which was > 1 order of magnitude greater than in the case of most of the other MoS 2 -based catalysts (Table S1). 1,3,4,6,7,11,14,16,31,32 …”
Section: Catalytic Performance Of 3d Structured S-depletedmentioning
confidence: 99%
“…Hinnemann et al [119] have shown that MoS 2 nanoparticles are good catalysts for the HER with an over potential as low as 0.1-0.2 V. Theoretical studies have revealed that the edge sites [120] and vacancies [121] in MoS 2 are catalytically active sites for HER. Enhanced photocatalytic and electrochemical HER activities have been achieved by increasing the surface area of or the density of active edge sites in the MoS 2 catalyst [122][123][124][125][126]. With the MoS 2 /graphene composite, electrocatalytic HER activity was further enhanced [127] due to a better electrical coupling to the electrode facilitated by graphene [128].…”
Section: Catalysismentioning
confidence: 99%
“…The turnover frequency of the Mo 2 C@N-CNF catalyst was estimated via previously reported methods. 35 Mo 2 C@N-CNFs achieve turnover frequencies of Figure S10), which is proportional to the effective electrochemical surface area. 37,38 The Mo 2 C@N-CNFs exhibit a high C dl of 11.34 mF cm − 2 at 0.22 V, which is slightly less than that of the high specific surface area vucan XC-72R carbon black-supported Pt catalyst (12.58 mF cm − 2 ) and comparable to those of many reported excellent non-precious HER catalysts, such as edge-terminated MoS 2 , 37 g-C 3 N 4 nanoribbon-graphene 39 and 3D CoSe 2 /carbon fiber felt.…”
Section: Synthesis Of a Mo 2 C-based Her Electrocatalyst Z-y Wu Et Almentioning
confidence: 99%